Index fund trading costs are inversely related to fund and family size - Adams, John; Hayunga, Darren; Mansi, Sattar (Journal of Banking & Finance, 2022)
Trading costs are a significant, but unobserved, drag on mutual fund performance. Because an index fund does not engage in securities selection or market timing, its trading costs are equivalent to its underperformance relative to its benchmark plus any securities lending income it earns. Using a large sample of index funds, we find positive returns to scale at the fund and family levels. We also find greater fund size helps alleviate the higher trading costs associated with illiquid equities and that net trading costs are comparable in magnitude to expense ratios.